IMPLICATIONS OH THE RELATIONSHIP BETWEEN THE CENTRAL GOVERNMENT AND LOCAL GOVERNMENTS AS A RESULT OF DISHARMONIZATION OF LOCAL REGULATIONS: IMPLIKASI HUBUNGAN PEMERINTAH PUSAT DAN PEMERINTAH DAERAH AKIBAT DISHARMONISASI PERATURAN DAERAH - Marella, Sarah; Firdaus, Fahmi Ramadhan (Pusat Studi Konstitusi dan Perundang-undangan, 2025)
Disharminization in local regulations occurs as a result of the phenomenon of over-regulation in Indonesia, which is growing increasingly prevalent. Findings in several regional regulations in Indonesia indicate that disharmony has a significant impact on the implementation of policies that directly affect the community. This issue of disharmony then has implications for the relationship between the central government and local governments as the authorities responsible for formulating and supervising local regulations. The central government is the main authority that controls the administration of the state throughout the territory, while local governments, acting in the name of regional autonomy, are the force that administers matters within their authority. Using a normative juridical method with conceptual, legislative, and comparative research types, this study finds common ground in the problems faced in the relationship between the central government and local governments regarding the issue of disharmony in regional regulations. These problems include the position of regional regulations in the framework of legislative theory, which is then viewed in comparison with Japan in organizing its legislation and the relationship between the central and regional governments in supervising regional regulations.